P P P : Paleo Psycho Pop - Healy, Patrick; Durham, Jimmie; Goldschmidt, Tijs; Haag, Philip; Manzetti, Barbara; Marchal, Patrick; Melgaard, Bjarne; St. Summiere, Bernard; Valle, Marian Del (Brussel : Edition Brussels, 1996)
Wäspi, Alfred ; Hofstede, Hilarius ; de Cordier, Thierry ; Denzler, Christian ; Peeters, Jacqueline ; Marchal, Patrick ; Melgaard, Bjarne ; Hoekstra, Berend ; Durham, Jimmie ; Schnider, Albrecht ; Krystopek, Elke ; Faussie, Laure ; Radulescu, Claudia ; Rebetez, Boris ; Valle, Marian Del ; Haag, Philip ; Paz, Emilia Simoes Da ; Goldschmidt, Tijs ; Fischer, Agnes ; Ris, Ernst ; Coppelmans, Domien
Duits
Engels
Frans
Nederlands
boek
Keywords: Hofstede, Hilarius